2002
DOI: 10.1002/1521-3773(20020916)41:18<3375::aid-anie3375>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step, Stereoselective Hydrazidoarylation of 1,3-Cyclopentadiene

Abstract: The first palladium-catalyzed reductive phenylation of norbornene (1) was published by Larock and Johnson [1] in 1989; since then the high synthetic potential of the hydroarylation [2] and especially its asymmetric variant [3] with bicyclic alkenes for the one-step construction of three asymmetric centers has induced a line of follow-up papers. This situation is especially true for the hydroarylation of the 7-aza-and oxabicyclic alkenes 2 (Scheme 1) [2b±d, 3c] as this synthetic route even in the case of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…(22)]. 33 Radhakrishnan and co‐workers reported the palladium(0)/Lewis acid mediated ring opening of azabicyclic olefin with organostannane, leading to the synthesis of 3,4‐disubstituted hydrazinocyclopentene derivative 49 in excellent yield 34. The reaction of phenyl boronic acid with bicyclic alkene in the presence of a Pd(OAc) 2 /PPh 3 /I 2 catalyst system afforded 3‐phenyl‐4‐hydrazino cyclopentene 48 [Eq.…”
Section: Reactions Of Deadmentioning
confidence: 99%
“…(22)]. 33 Radhakrishnan and co‐workers reported the palladium(0)/Lewis acid mediated ring opening of azabicyclic olefin with organostannane, leading to the synthesis of 3,4‐disubstituted hydrazinocyclopentene derivative 49 in excellent yield 34. The reaction of phenyl boronic acid with bicyclic alkene in the presence of a Pd(OAc) 2 /PPh 3 /I 2 catalyst system afforded 3‐phenyl‐4‐hydrazino cyclopentene 48 [Eq.…”
Section: Reactions Of Deadmentioning
confidence: 99%
“…[7] Conversely, the racemic hydroarylation of diazabicycles using Pd was reported by Kaufmann and co-workers, but the reaction led to mixtures of 2 and 3. [8] We found that the hydroarylation products are formed through a mechanism that is markedly different from the one proposed with Pd, thus opening up new synthetic opportunities. [9] We focused on finding a solution to the challenging problem of enantioselective ring-opening of diazabicyclo-[2.2.1]heptanes to provide a rapid synthesis of optically active trans-2-arylated cyclopentyl amines 4, which are known to be biologically active small molecules (Scheme 1).…”
mentioning
confidence: 90%
“…by various research groups . Kaufmann and co‐workers explored the palladium catalyzed hydroarylation of diazabicyclic olefins . Our group has demonstrated the utility of mono and bi‐functional aryl iodides with diazabicyclic olefins toward the construction of 3,4‐disubstituted cyclopentenes, indanones and indoline/benzofuran fused cyclopentenes…”
Section: Introductionmentioning
confidence: 99%
“…[8] Kaufmann and co-workers explored the palladium catalyzed hydroarylation of diazabicyclic olefins. [9] Our group has demonstrated the utility of mono and bi-functional aryl iodides with diazabicyclic olefins toward the construction of 3,4-disubstituted cyclopentenes, [10] indanones [11] and indoline/ benzofuran fused cyclopentenes. [12] Urea and its cyclic derivatives represent a class of biologically relevant molecules, widely occurring in natural products and have been studied for various biological activities such as antibiotic hypoglycemic effects, anti-cancer, antidiabetic, antimicrobial, antibacterial activities etc.…”
Section: Introductionmentioning
confidence: 99%